CINNAMON EXTRACT PROVIDES MORE NEPHROPROTECTION THAN GREEN TEA IN BISPHENOL - A INDUCED DAMAGE IN PROXIMAL AND DISTAL KIDNEY TUBULES - Beenish, Huma; Rana, Rehana; Ali, Shabana (Pakistan Armed Forces Medical Journal, 2019)
Objective: To compare protective potential of cinnamon extract and green tea against Bisphenol A induced changes in tubular histology of rat kidney.Design of Study: Randomized controlled trial.Place and Duration of Study: Duration of study was six months and was conducted in Islamic International Medical College in collaboration with NIH.Material and Methods: Sixty adult male rats of Sprague Dawley strain were placed in 4 cages having 15 rats each. Experimental duration was 30 days. Rats in control group A were subcutaneously injected with distilled water. Rats in experimental group B were given subcutaneous injections of BPA at dose of 30mg/kg/day. Rats in group C were given cinnamon (200mg/kg/day) orally along with s/c injection of BPA while group D rats were given green tea orally along with s/c BPA injections. All rats were dissected after 30 days and right kidneys were taken out to examine histological changes in proximal and distal convoluted tubules.Results: Histological parameters of proximal and distal convoluted tubules were observed in experimental and control groups. Marked deterioration of tubular structure was observed in group B as compared to control group. Although both groups C and D showed nephroprotection against tubular histological changes but group D offered greater nephroprotection than group C.Conclusion: Green tea was more effective than cinnamon in combating the oxidative stress induced neprotoxicity caused by BPA. Co-administration of cinnamon and green tea with BPA reduced the histological damage in proximal and distal convoluted tubules of nephrons in rats caused by Bisphenol A.